GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PENDERITA TUBERCULOSIS (TBC) DI WILAYAH KERJA UPTD PUSKESMAS PUNGGELAN 1 TAHUN 2024 - Bayu Suseno; Yolanda Syifa Amalia (Jurnal Ilmiah Medsains, 2025)
Tuberculosis (TB) is an infectious disease caused by the Tuberculosis germ (Mycobacterium Tuberculosis). Tuberculosis is included in 10 environment- based infectious diseases in the 3rd rank in the working area of the Punggelan 1 Health Center. The purpose of this study is to find out the overview of knowledge, attitudes and behaviors of TB patients towards the disease, prevention and treatment of TB in the work area of UPTD Pukesmas Punggelan 1. This study is a descriptive research with a cross sectional method and by interview method with a sample of 47 respondents. The variables studied were the characteristics of the respondents (age, gender, education, occupation) , home condition of the patient as well as knowledge, attitude and behavior. This research was carried out in May-June 2024, located in the work area of the UPTD Punggelan 1 Health Center. The results of the study showed that the age characteristics of the respondents were most commonly found in the adult age category (1) 76.6%, male 61.7%, low education level 80.9%, the type of work the majority of workers 34.0%, and the condition of the patient's home with the unhealthy category of 87.2%. Meanwhile, the respondents' knowledge about tuberculosis and prevention and treatment was in the good category of 83.0%, the respondent's attitude was classified as good 89.4%, and the respondent's behavior was good 93.6% The conclusion of this study is that the knowledge, attitudes and behaviors of the largest respondents are in the good category, but there are still many respondents' houses with unhealthy house categories. The Punggelan 1 Health Center needs to carry out follow-up programs to increase awareness of the importance of a healthy home environment in the prevention and treatment of tuberculosis as well as conduct routine monitoring and periodically evaluate the programs that have been running to ensure their effectiveness.